High-toughness wear-resistant titanium-based composite material and preparation method thereof
By using a variety of alloy elements and reinforced phases in titanium-based composite materials, combined with vacuum suspension smelting and isothermal forging processes, the problem of insufficient toughness and wear resistance in complex environments is solved, and the performance improvement of high strength, toughness, wear resistance is achieved.
Patent Information
- Application Number
- CN202411995548.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The existing titanium-based composite materials have not yet met the requirements of high toughness and wear resistance in complex and harsh environments such as high temperature, high speed, and high load. It is urgent to develop high-strength, tough, wear-resistant titanium-based composite materials with better performance.
A matrix composed of a variety of alloy elements (such as Al, Nb, Fe, Mo, V, Zr) is used, and reinforced phases such as TiB, TiC, La2O3 are added through vacuum suspension smelting and isothermal forging processes to form a high-strength, tough, wear-resistant titanium-based composite material.
It significantly improves the strength, toughness and wear resistance of the material, and is suitable for complex environments such as high temperature, high speed, and high load, extends service life and reduces energy consumption.
Smart Images

Figure CN119776699A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of composite materials, and more specifically to a high-strength, toughness, and wear-resistant titanium-based composite material and a preparation method thereof. Background Art
[0002] With the development of economy and society, the limitation of resources and energy has gradually become prominent, and the performance requirements of materials in various industries have been continuously improved. For example, in the fields of automobiles and engineering machinery, in order to achieve lightweight and maintain good performance, high-strength and wear-resistant materials are needed to reduce dead weight, improve fuel efficiency and extend service life. For example, in industrial production, many mechanical parts such as steel balls in mills and crankshafts of engines work under high-speed, high-load and high-friction conditions, which have strict requirements on the strength and wear resistance of materials, prompting scientific researchers to develop high-strength and wear-resistant materials with better performance. For example, in the fields of marine engineering and chemical industry, materials face the dual challenges of corrosion and wear, and the development of high-strength, wear-resistant and corrosion-resistant materials has become the key to solving related problems. In addition, in the field of aerospace, the performance requirements of materials are also extremely high, such as aircraft engines, spacecraft structural parts, etc., which must be lightweight and have high strength, high toughness and good high temperature resistance.
[0003] Compared with traditional high-strength, tough and wear-resistant materials, titanium-based composites have shown remarkable performance characteristics: (1) Titanium-based composites have a lower density, which gives them a significant advantage in manufacturing lightweight components. For example, in the fields of aerospace and automobile manufacturing, lightweighting is a key way to reduce energy consumption and improve performance. Titanium-based composites can significantly reduce the weight of components, thereby reducing energy consumption and improving overall performance. (2) Titanium-based composites have higher strength, which allows them to maintain good structural stability under extreme conditions such as high loads and high pressures. Ensure the safety and reliability of components. (3) Titanium-based composites also exhibit excellent corrosion resistance and can maintain the long-term stability of material properties.
[0004] Although titanium-based composites have many advantages, with the continuous development of aerospace, automobile manufacturing and other fields, titanium-based composites have higher requirements for toughness and wear resistance. Therefore, it is urgent to develop high-strength, toughness and wear-resistant titanium-based composites with better performance to meet the requirements of use in more complex and harsh environments such as high temperature, high speed and high load. Summary of the invention
[0005] The present application provides a high-strength, toughness, and wear-resistant titanium-based composite material and a preparation method thereof to meet the use requirements in more complex and harsh environments such as high temperature, high speed, and high load.
[0006] The implementation process of the present invention is as follows:
[0007] The invention provides a high-strength, tough and wear-resistant titanium-based composite material, comprising a matrix and a reinforcement phase, wherein the matrix comprises the following elemental components in mass percentage: Al 5.6-7%, Nb 2.9-4%, Fe 1.8-3%, Mo 1.5-2%, V 1.4-2%, Zr 0.9-1.5% and the balance Ti; the reinforcement phase is selected from at least two of TiB, TiC or La2O3, and the mass percentage of the reinforcement phase in the titanium-based composite material is 0.3-3%.
[0008] The above-mentioned high-strength, toughness and wear-resistant titanium-based composite material preferably includes a matrix and a reinforcement phase, wherein the matrix includes the following elemental components in mass percentage: Al 5.7%, Nb 2.9%, Fe 1.8%, Mo 1.6%, V 1.5%, Zr 0.92% and the remainder is Ti; the reinforcement phase is TiB and La2O3, and the mass percentage of the reinforcement phase in the titanium-based composite material is 0.3-1.2%.
[0009] The preparation method of the above-mentioned high-strength, toughness and wear-resistant titanium-based composite material comprises the following steps: (1) configuring raw materials according to the mass percentage of the elemental components of the matrix, and then adding a reinforcing phase to obtain an alloy mixture; (2) subjecting the alloy mixture to vacuum suspension melting to obtain a titanium-based composite material ingot; (3) transferring the ingot to a forging machine for isothermal forging after heat preservation in the α+β phase region to obtain a high-strength, toughness and wear-resistant titanium-based composite material.
[0010] Furthermore, in step (1), the elemental composition of the matrix comprises by weight 5.6-7% Al, 2.9-4% Nb, 1.8-3% Fe, 1.5-2% Mo, 1.4-2% V, 0.9-1.5% Zr and the remainder Ti; the reinforcing phase is selected from at least two of TiB, TiC or La2O3, and the weight percentage of the reinforcing phase in the titanium-based composite material is 0.3-3%.
[0011] Furthermore, in step (2), the specific process of the vacuum suspension smelting includes the following steps: (2.1) placing the alloy mixture in a crucible; (2.2) evacuating the furnace of a vacuum water-cooled copper crucible suspension smelting furnace, filling it with argon, and turning on the power; (2.3) smelting at a power of 75 to 155 kW, and then refining at a power of 145 to 155 kW; (2.4) turning the alloy over and repeating the smelting and refining process for at least 5 times until the alloy is evenly smelted. After the refining is completed, the furnace is naturally cooled, the gas is released from the furnace, and an ingot of a titanium-based composite material is obtained.
[0012] Furthermore, in step (3), the process of transferring the casting to the forging machine for isothermal forging after heat preservation is to place the titanium-based composite material ingot in a muffle furnace and heat it to the α+β phase region for heat preservation, while heating the upper and lower molds of the forging machine to the α+β phase region temperature, transferring the casting from the muffle furnace to the forging machine for a forging, and air cooling after forging to obtain a high-strength, toughness and wear-resistant titanium-based composite material.
[0013] Furthermore, in step (1), the elements Ti, Al, Nb, Fe, Mo, V, and Zr in the matrix are added in the form of sponge titanium, high-purity aluminum, niobium-titanium alloy, iron particles, titanium-molybdenum alloy, vanadium-aluminum alloy, and sponge zirconium, respectively; and TiB, TiC, and La2O3 in the reinforcement phase are added in the form of titanium diboride, graphite powder, and lanthanum oxide, respectively.
[0014] Furthermore, the titanium diboride and the graphite powder are synthesized into TiB and TiC respectively through in-situ autogenous reaction, and the in-situ autogenous reaction is shown in the following formula: Ti+TiB2=2TiB, Ti+C=TiC.
[0015] Furthermore, the vacuum degree in step (2.2) is 3×10 -2 ~5×10 -2 Pa, filled with argon 0.05~0.1MPa.
[0016] Furthermore, in the step (2.3), the smelting process is carried out at powers of 75-85kw, 95-105kw, 115-125kw, and 145-155kw in sequence, and then refined at a power of 145-155kw.
[0017] Further, in the step (2.3), the specific process of the smelting is smelting at a power of 75 to 85 kw for 4 to 6 minutes, smelting at a power of 95 to 105 kw for 4 to 6 minutes, smelting at a power of 115 to 125 kw for 4 to 6 minutes, smelting at a power of 145 to 155 kw for 4 to 6 minutes, and then refining at a power of 145 to 155 kw for 4 to 6 minutes.
[0018] Furthermore, the deformation amount of the forging is not less than 60%.
[0019] Furthermore, the pretreatment process of the titanium-based composite material ingot is to first cut a cylindrical casting on the titanium-based composite material ingot by wire cutting; then evenly apply high-temperature anti-oxidation coating on the surface of the casting, wrap the casting with asbestos after drying, and bundle it.
[0020] Furthermore, the high temperature anti-oxidation coating is Ti-1200 high temperature anti-oxidation coating.
[0021] Positive effects of the present invention:
[0022] (1) The matrix of the high-strength, toughness and wear-resistant titanium-based composite material prepared by the present invention is new. Different from conventional α+β titanium alloy, it adopts more types of alloy elements, including α-stabilizing element Al, neutral element Zr, β-stabilizing elements Fe, Nb, V, and Mo. These multiple elements play the role of lowering the phase transition point temperature and supplementing the strength. At the same time, two or three of the reinforcing phases TiB, TiC, and La2O3 are used for synergistic strengthening. Among them, TiB and TiC have excellent performance, and their physical properties such as density and thermal expansion coefficient are relatively close to Ti, which is helpful to obtain high-quality titanium-based composite materials. Rare earth oxide La2O3 is conducive to grain refinement, improving fatigue resistance, and improving thermal stability. In addition, although the high-strength, toughness and wear-resistant titanium-based composite material prepared by the present invention does not use too many expensive alloy elements, it also achieves the improvement of the comprehensive performance of the composite material.
[0023] (2) The method for preparing the high-strength, toughness and wear-resistant titanium-based composite material of the present invention utilizes isothermal forging deformation to refine and improve the structure and reinforcement phase, thereby improving the performance; and the forging is performed in one step, and the process is simple.
[0024] It should be understood that the foregoing general description and the following detailed description are exemplary only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The accompanying drawings, which are incorporated herein and form a part of the specification, illustrate one or more embodiments of the present application and, together with the description, serve to explain the principles of the present application and to enable one of ordinary skill in the relevant art to make and use the present application.
[0026] Figure 1 This is a flow chart of the preparation method of the high-strength, toughness and wear-resistant titanium-based composite material of the present invention;
[0027] Figure 2 is the engineering stress-strain curve of TMC4;
[0028] Figure 3 Optical microscope images of TMC0-TMC5 as-cast;
[0029] Figure 4 SEM images of TMC0-TMC5 as-cast;
[0030] Figure 5 It is an optical microscope image of TMC0-TMC5 forging state;
[0031] Figure 6 SEM images of TMC0-TMC5 forged states;
[0032] Figure 7 This is the element surface distribution diagram of TMC3. DETAILED DESCRIPTION
[0033] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments may be implemented in a variety of forms and should not be construed as being limited to the examples set forth herein; rather, the description of these embodiments is intended to make the present application more comprehensive and complete and to fully convey the concepts of the example embodiments to those skilled in the art. The described features, structures, or characteristics may be combined in any suitable manner in one or more embodiments. In the following description, many specific details are provided to provide a deeper understanding of the embodiments of the present application.
[0034] The invention provides a high-strength, tough and wear-resistant titanium-based composite material, comprising a matrix and a reinforcement phase, wherein the matrix comprises the following elemental components in percentage by mass: 5.6-7% Al, 2.9-4% Nb, 1.8-3% Fe, 1.5-2% Mo, 1.4-2% V, 0.9-1.5% Zr and the balance is Ti; the elements Ti, Al, Nb, Fe, Mo, V and Zr in the matrix are added in the form of sponge titanium, high-purity aluminum, niobium-titanium alloy, iron particles, titanium-molybdenum alloy, vanadium-aluminum alloy and sponge zirconium respectively.
[0035] The reinforcing phase is selected from at least two of TiB, TiC or La2O3, and the mass percentage of the reinforcing phase in the titanium-based composite material is 0.3-3%. The TiB, TiC and La2O3 in the reinforcing phase are added in the form of titanium diboride, graphite powder and lanthanum oxide respectively. The titanium diboride and the graphite powder are synthesized into TiB and TiC respectively by in-situ autogenous reaction, and the in-situ autogenous reaction is shown as follows: Ti+TiB2=2TiB, Ti+C=TiC. Among them, the density of TiB is 4.50g / cm 3 , the density of TiC is 4.99g / cm 3 The density of La2O3 is 6.51 g / cm 3 The relative atomic masses of the elements required for calculation in the present invention are: B: 10.81, C: 12.01, Ti: 47.87, O: 16.00, La: 138.91.
[0036] Preferably, the high-strength, toughness and wear-resistant titanium-based composite material comprises a matrix and a reinforcement phase, wherein the matrix comprises the following elemental components in mass percentage: Al 5.7%, Nb 2.9%, Fe 1.8%, Mo 1.6%, V 1.5%, Zr 0.92% and the balance Ti;
[0037] The reinforcement phase is TiB and La2O3, and the mass percentage of the reinforcement phase in the titanium-based composite material is 0.3-1.2%.
[0038] The matrix of the high-strength, tough and wear-resistant titanium-based composite material prepared by the present invention is new. Different from conventional α+β titanium alloy, it adopts more types of alloy elements, including α-stabilizing element Al, neutral element Zr, β-stabilizing elements Fe, Nb, V, Mo, and the multiple elements play the role of reducing the phase transition point temperature and supplementing the strength. At the same time, two or three of the reinforcing phases TiB, TiC, and La2O3 are used for synergistic strengthening, among which TiB and TiC have excellent performance, and their physical properties such as density and thermal expansion coefficient are relatively close to Ti, which is helpful to obtain high-quality titanium-based composite materials, and the rare earth oxide La2O3 is conducive to grain refinement, improving fatigue resistance, and improving thermal stability. In addition, although the high-strength, tough and wear-resistant titanium-based composite material prepared by the present invention does not use too many expensive alloy elements, it also achieves the improvement of the comprehensive performance of the composite material.
[0039] The present invention also provides a method for preparing the high-strength, toughness and wear-resistant titanium-based composite material. Figure 1 , including the following steps:
[0040] (1) preparing raw materials according to the mass percentage of the elemental components of the matrix, and then adding a reinforcing phase to obtain an alloy mixture;
[0041] The mass percentage of the element composition of the matrix is Al 5.6-7%, Nb 2.9-4%, Fe 1.8-3%, Mo 1.5-2%, V 1.4-2%, Zr 0.9-1.5% and the balance is Ti; the elements Ti, Al, Nb, Fe, Mo, V and Zr in the matrix are added in the form of sponge titanium, high-purity aluminum, niobium-titanium alloy, iron particles, titanium-molybdenum alloy, vanadium-aluminum alloy and sponge zirconium respectively;
[0042] The reinforcing phase is selected from at least two of TiB, TiC or La2O3, and the mass percentage of the reinforcing phase in the titanium-based composite material is 0.3-3%. The TiB, TiC and La2O3 in the reinforcing phase are added in the form of titanium diboride, graphite powder and lanthanum oxide respectively. The titanium diboride and the graphite powder are synthesized into TiB and TiC respectively through in-situ autogenous reaction, and the in-situ autogenous reaction is shown in the following formula: Ti+TiB2=2TiB, Ti+C=TiC.
[0043] (2) obtaining a titanium-based composite ingot by vacuum suspension melting the alloy mixture;
[0044] The specific process of vacuum suspension smelting includes the following steps:
[0045] (2.1) Placing the alloy mixture in a crucible;
[0046] (2.2) The vacuum degree in the vacuum water-cooled copper crucible suspension melting furnace was reduced to 3×10 -2 ~5×10 -2Pa, fill with argon 0.05~0.1MPa, turn on the power;
[0047] (2.3) Melt at a power of 75-155kw until the alloy is melted evenly;
[0048] The specific process of the smelting is smelting at a power of 75 to 85 kw for 4 to 6 minutes, smelting at a power of 95 to 105 kw for 4 to 6 minutes, smelting at a power of 115 to 125 kw for 4 to 6 minutes, smelting at a power of 145 to 155 kw for 4 to 6 minutes, and then refining at a power of 145 to 155 kw for 4 to 6 minutes.
[0049] (2.4) The alloy is turned over and the melting and refining process is repeated for at least 5 times until the alloy is melted evenly. After the refining is completed, the furnace is naturally cooled, the gas is released and the furnace is taken out to obtain a titanium-based composite ingot.
[0050] The vacuum water-cooled copper crucible suspension smelting furnace of the present invention is a ZG2-XF 5KG vacuum water-cooled copper crucible suspension smelting furnace. In addition, other models or manufacturers of suspension smelting furnaces can also be selected as long as they meet the smelting requirements of the present invention and produce the effects of the present invention.
[0051] (3) After the ingot is kept warm in the α+β phase region, it is transferred to a forging machine for isothermal forging to obtain a high-strength, toughness, and wear-resistant titanium-based composite material.
[0052] Among them, the process of transferring to the forging machine for isothermal forging after insulation is to place the titanium-based composite material ingot in a muffle furnace and heat it to the α+β phase region for insulation, while heating the upper and lower molds of the forging machine to the α+β phase region temperature, and transferring the casting from the muffle furnace to the forging machine for one forging, the deformation of the forging is not less than 60%, and air cooling after forging is completed to obtain a high-strength, toughness and wear-resistant titanium-based composite material.
[0053] The pretreatment process of the titanium-based composite material ingot is to first cut a cylindrical casting on the titanium-based composite material ingot by wire cutting; then evenly apply Ti-1200 high-temperature anti-oxidation coating on the surface of the casting, wrap the casting with asbestos after drying, and bundle it.
[0054] The muffle furnace in the present invention adopts ZY-1200 muffle furnace. In addition to the muffle furnace of the model described in the present invention, muffle furnaces of other manufacturers and models can also be used as long as the heating and heat preservation effect can be achieved. The forging machine adopts 400-ton Y01532323-400 four-column hydraulic forging machine. In addition to the forging machine of the model described in the present invention, forging machines of other manufacturers and models can also be used as long as the forging temperature described in the present invention can be reached and the forging effect described in the present invention can be achieved.
[0055] In the forging and subsequent processing of the matrix alloy and titanium-based composite material of the present invention, the α+β~β phase transition temperature plays an important reference role, so this parameter must be considered when designing forging and other processing technologies. The presence of elements such as aluminum, vanadium, zirconium, and iron in the titanium-based composite material will affect its α+β~β phase transition temperature, and impurity elements such as carbon, hydrogen, oxygen, and nitrogen will also affect its phase transition temperature. In order to provide a scientific basis for subsequent experimental research, the α+β~β phase transition temperature of the Ti-5.7Al-2.9Nb-1.8Fe-1.6Mo-1.5V-0.92Zr matrix alloy was measured by differential scanning calorimetry (DSC) to be 950°C, and the α+β~β phase transition temperature of the titanium-based composite material was measured by continuous heating metallographic method to be between 1000 and 1025°C. The present invention uses forging technology after smelting to enhance the density of the titanium-based composite material.
[0056] The preparation method of the high-strength, toughness and wear-resistant titanium-based composite material provided by the present invention utilizes isothermal forging deformation to refine and improve the organization and reinforcement phase, thereby improving the performance; and the method is formed by one-time forging, has a simple process and has a prospect for promotion and application.
[0057] The specifications of the raw materials involved in the present invention are shown in Table 1.
[0058] Table 1 Specifications of raw materials used in the experiment
[0059]
[0060]
[0061] Comparative Example 1 Matrix Alloy TMC0
[0062] The base alloy includes the following element compositions in mass percentage: Al 5.7%, Nb 2.9%, Fe 1.8%, Mo 1.6%, V 1.5%, Zr 0.92% and the balance Ti.
[0063] The preparation method of the substrate comprises the following steps:
[0064] (1) According to the mass percentage of the elemental components of the matrix alloy, 796.08 g of sponge titanium, 47.00 g of high-purity aluminum, 54.72 g of niobium-titanium alloy (Ti-53Nb), 18.00 g of iron particles, 25.00 g of vanadium-aluminum alloy (Al-60V), 50.00 g of titanium-molybdenum alloy (Ti-32Mo), and 9.20 g of sponge zirconium were added to obtain a matrix alloy mixture.
[0065] (2) melting the matrix alloy mixture by vacuum arc melting to obtain a matrix alloy ingot;
[0066] The parameters of the vacuum arc melting process are as follows:
[0067] (2.1) Placing the matrix alloy mixture in a crucible;
[0068] (2.2) The matrix alloy mixture is subjected to the first vacuum arc melting, the vacuum degree in the vacuum arc melting furnace is evacuated to <10Pa, the melting current range is 500-2500A, the arc stabilization current range is 1-6A, the arc stabilization voltage range is 10-40V, and the melting time is 5 minutes;
[0069] (2.3) The alloy is turned over and subjected to vacuum arc melting for the second time. The vacuum degree in the vacuum arc melting furnace is evacuated to <10Pa, the melting current range is 500-4500A, the arc stabilization current range is 1-6A, the arc stabilization voltage range is 10-40V, and the melting time is 5 minutes. After the melting is completed, the furnace is naturally cooled, the gas is released from the furnace, and the matrix alloy ingot is obtained.
[0070] (3) First, use wire cutting to cut out the base alloy ingot. The cylindrical casting is then evenly coated with Ti-1200 high temperature anti-oxidation coating on the surface of the casting, and after drying, the casting is wrapped with asbestos and tied with fine iron wire to prevent the asbestos from falling off; the casting is then placed in a muffle furnace and heated to 940°C for 30 minutes, while the upper and lower dies of the forging machine are heated to 940°C, and the casting is transferred from the muffle furnace to the forging machine at a speed of 0.01s -1 The forging speed is 10000, and the deformation of the forging is not less than 60%. After forging, it is air-cooled to obtain the base alloy, which is numbered as TMC0. The density of the base alloy TMC0 needs to be tested by the Archimedean drainage method. The final density of the base alloy is 4.55g / cm 3 .
[0071] Example 1 High-strength, toughness, and wear-resistant titanium-based composite material TMC1
[0072] The high-strength, toughness and wear-resistant titanium-based composite material of this embodiment comprises a matrix and a reinforcement phase, wherein the matrix comprises the following elemental components in mass percentage: Al 5.7%, Nb 2.9%, Fe 1.8%, Mo 1.6%, V 1.5%, Zr 0.92% and the balance Ti;
[0073] The reinforcing phases are TiB and La2O3. The mass percentage of the reinforcing phase TiB in the titanium-based composite material is 2.47%, and the mass percentage of La2O3 is 0.285%.
[0074] The method for preparing the high-strength, toughness and wear-resistant titanium-based composite material described in this embodiment comprises the following steps:
[0075] (1) According to the mass percentage of the elemental components of the matrix, raw materials including sponge titanium 784.21 g, high-purity aluminum 45.70 g, niobium-titanium alloy (Ti-53Nb) 53.21 g, iron particles 17.50 g, vanadium-aluminum alloy (Al-60V) 24.31 g, titanium-molybdenum alloy (Ti-32Mo) 48.62 g, and sponge zirconium 8.95 g are added, and then reinforcing phase titanium diboride 14.63 g and lanthanum oxide 2.86 g are added to obtain an alloy mixture; the titanium diboride is synthesized into TiB by an in-situ autogenous reaction, and the in-situ autogenous reaction is shown as follows: Ti+TiB2=2TiB.
[0076] (2) obtaining a titanium-based composite ingot by vacuum suspension melting the alloy mixture;
[0077] The specific process of vacuum suspension smelting includes the following steps:
[0078] (2.1) Placing the alloy mixture in a crucible;
[0079] (2.2) The vacuum degree in the vacuum water-cooled copper crucible suspension melting furnace was reduced to 3.8×10 -2 Pa, fill with argon 0.08MPa, turn on the power;
[0080] (2.3) melting at 80 kW for 5 minutes, melting at 100 kW for 5 minutes, melting at 120 kW for 5 minutes, melting at 150 kW for 5 minutes, and then refining at 150 kW for 5 minutes;
[0081] (2.4) The alloy is turned over and the melting and refining process is repeated 5 times until the alloy is melted evenly. After the refining is completed, the furnace is naturally cooled, the gas is released and the furnace is taken out to obtain a titanium-based composite ingot.
[0082] (3) First, wire cutting is used to cut out the titanium-based composite ingot. The cylindrical casting is then evenly coated with Ti-1200 high temperature anti-oxidation coating on the surface of the casting, and after drying, the casting is wrapped with asbestos and tied with fine iron wire to prevent the asbestos from falling off; the casting is then placed in a muffle furnace and heated to 940°C for 30 minutes, while the upper and lower dies of the forging machine are heated to 940°C, and the casting is transferred from the muffle furnace to the forging machine at a speed of 0.01s -1 The forging is performed once at a speed of , the deformation amount of forging is not less than 60%, and air cooling is performed after forging to obtain a high-strength, toughness and wear-resistant titanium-based composite material, which is numbered TMC1.
[0083] Example 2 High-strength, toughness, and wear-resistant titanium-based composite material TMC2
[0084] The high-strength, toughness and wear-resistant titanium-based composite material of this embodiment comprises a matrix and a reinforcement phase, wherein the matrix comprises the following elemental components in mass percentage: Al 5.7%, Nb 2.9%, Fe 1.8%, Mo 1.6%, V 1.5%, Zr 0.92% and the balance Ti;
[0085] The reinforcing phases are TiB, TiC and La2O3. The mass percentage of the reinforcing phase TiB in the titanium-based composite material is 1.23%, the mass percentage of TiC is 1.37%, and the mass percentage of La2O3 is 0.285%.
[0086] The method for preparing the high-strength, toughness and wear-resistant titanium-based composite material described in this embodiment comprises the following steps:
[0087] (1) According to the mass percentage of the elemental components of the matrix, 789.07 g of raw materials of sponge titanium, 45.64 g of high-purity aluminum, 53.14 g of niobium-titanium alloy (Ti-53Nb), 17.48 g of iron particles, 24.28 g of vanadium-aluminum alloy (Al-60V), 48.56 g of titanium-molybdenum alloy (Ti-32Mo), and 8.93 g of sponge zirconium are added, and then 7.31 g of reinforcing phase titanium diboride, 2.74 g of graphite powder, and 2.86 g of lanthanum oxide are added to obtain an alloy mixture; the titanium diboride and the graphite powder are synthesized into TiB and TiC respectively through in-situ autogenous reactions, and the in-situ autogenous reactions are shown as follows: Ti+TiB2=2TiB, Ti+C=TiC.
[0088] (2) obtaining a titanium-based composite ingot by vacuum suspension melting the alloy mixture;
[0089] The specific process of vacuum suspension smelting includes the following steps:
[0090] (2.1) Placing the alloy mixture in a crucible;
[0091] (2.2) The vacuum degree in the vacuum water-cooled copper crucible suspension melting furnace was reduced to 3.8×10 -2 Pa, fill with argon 0.08MPa, turn on the power;
[0092] (2.3) melting at 80 kW for 5 minutes, melting at 100 kW for 5 minutes, melting at 120 kW for 5 minutes, melting at 150 kW for 5 minutes, and then refining at 150 kW for 5 minutes;
[0093] (2.4) The alloy is turned over and the melting and refining process is repeated 5 times until the alloy is melted evenly. After the refining is completed, the furnace is naturally cooled, the gas is released and the furnace is taken out to obtain a titanium-based composite ingot.
[0094] (3) First, wire cutting is used to cut out the titanium-based composite ingot. The cylindrical casting is then evenly coated with Ti-1200 high temperature anti-oxidation coating on the surface of the casting, and after drying, the casting is wrapped with asbestos and tied with fine iron wire to prevent the asbestos from falling off; the casting is then placed in a muffle furnace and heated to 940°C for 30 minutes, while the upper and lower dies of the forging machine are heated to 940°C, and the casting is transferred from the muffle furnace to the forging machine at a speed of 0.01s -1 The forging is performed once at a speed of , the deformation during forging is not less than 60%, and air cooling is performed after forging to obtain a high-strength, toughness and wear-resistant titanium-based composite material, which is numbered TMC2.
[0095] Example 3 High-strength, toughness, and wear-resistant titanium-based composite material TMC3
[0096] The high-strength, toughness and wear-resistant titanium-based composite material of this embodiment comprises a matrix and a reinforcement phase, wherein the matrix comprises the following elemental components in mass percentage: Al 5.7%, Nb 2.9%, Fe 1.8%, Mo 1.6%, V 1.5%, Zr 0.92% and the balance Ti;
[0097] The reinforcing phases are TiB and La2O3. The mass percentage of the reinforcing phase TiB in the titanium-based composite material is 0.247%, and the mass percentage of La2O3 is 0.143%.
[0098] The method for preparing the high-strength, toughness and wear-resistant titanium-based composite material described in this embodiment comprises the following steps:
[0099] (1) According to the mass percentage of the elemental components of the matrix, 793.99 g of raw materials including sponge titanium, 46.82 g of high-purity aluminum, 54.50 g of niobium-titanium alloy (Ti-53Nb), 17.93 g of iron particles, 24.90 g of vanadium-aluminum alloy (Al-60V), 49.80 g of titanium-molybdenum alloy (Ti-32Mo), and 9.16 g of sponge zirconium are added, and then 1.46 g of reinforcing phase titanium diboride and 1.43 g of lanthanum oxide are added to obtain an alloy mixture; the titanium diboride is synthesized into TiB by an in-situ autogenous reaction, and the in-situ autogenous reaction is shown as follows: Ti+TiB2=2TiB.
[0100] (2) obtaining a titanium-based composite ingot by vacuum suspension melting the alloy mixture;
[0101] The specific process of vacuum suspension smelting includes the following steps:
[0102] (2.1) Placing the alloy mixture in a crucible;
[0103] (2.2) The vacuum degree in the vacuum water-cooled copper crucible suspension melting furnace was reduced to 3.8×10 -2 Pa, fill with argon 0.08MPa, turn on the power;
[0104] (2.3) melting at 80 kW for 5 minutes, melting at 100 kW for 5 minutes, melting at 120 kW for 5 minutes, melting at 150 kW for 5 minutes, and then refining at 150 kW for 5 minutes;
[0105] (2.4) The alloy is turned over and the melting and refining process is repeated 5 times until the alloy is melted evenly. After the refining is completed, the furnace is naturally cooled, the gas is released and the furnace is taken out to obtain a titanium-based composite ingot.
[0106] (3) First, wire cutting is used to cut out the titanium-based composite ingot. The cylindrical casting is then evenly coated with Ti-1200 high temperature anti-oxidation coating on the surface of the casting, and after drying, the casting is wrapped with asbestos and tied with fine iron wire to prevent the asbestos from falling off; the casting is then placed in a muffle furnace and heated to 940°C for 30 minutes, while the upper and lower dies of the forging machine are heated to 940°C, and the casting is transferred from the muffle furnace to the forging machine at a speed of 0.01s -1 The forging is performed once at a speed of , the deformation amount of forging is not less than 60%, and air cooling is performed after forging to obtain a high-strength, toughness and wear-resistant titanium-based composite material, which is numbered TMC3.
[0107] Example 4 High-strength, toughness, and wear-resistant titanium-based composite material TMC4
[0108] The high-strength, toughness and wear-resistant titanium-based composite material of this embodiment comprises a matrix and a reinforcement phase, wherein the matrix comprises the following elemental components in mass percentage: Al 5.7%, Nb 2.9%, Fe 1.8%, Mo 1.6%, V 1.5%, Zr 0.92% and the balance Ti;
[0109] The reinforcing phases are TiB and La2O3. The mass percentage of the reinforcing phase TiB in the titanium-based composite material is 0.494%, and the mass percentage of La2O3 is 0.143%.
[0110] The method for preparing the high-strength, toughness and wear-resistant titanium-based composite material described in this embodiment comprises the following steps:
[0111] (1) According to the mass percentage of the elemental components of the matrix, raw materials including sponge titanium 793.03 g, high-purity aluminum 46.70 g, niobium-titanium alloy (Ti-53Nb) 54.37 g, iron particles 17.89 g, vanadium-aluminum alloy (Al-60V) 24.84 g, titanium-molybdenum alloy (Ti-32Mo) 49.68 g, and sponge zirconium 9.14 g are added, and then reinforcing phase titanium diboride 2.93 g and lanthanum oxide 1.43 g are added to obtain an alloy mixture; the titanium diboride is synthesized into TiB by an in-situ autogenous reaction, and the in-situ autogenous reaction is shown as follows: Ti+TiB2=2TiB.
[0112] (2) obtaining a titanium-based composite ingot by vacuum suspension melting the alloy mixture;
[0113] The specific process of vacuum suspension smelting includes the following steps:
[0114] (2.1) Placing the alloy mixture in a crucible;
[0115] (2.2) The vacuum degree in the vacuum water-cooled copper crucible suspension melting furnace was reduced to 3.8×10 -2 Pa, fill with argon 0.08MPa, turn on the power;
[0116] (2.3) melting at 80 kW for 5 minutes, melting at 100 kW for 5 minutes, melting at 120 kW for 5 minutes, melting at 150 kW for 5 minutes, and then refining at 150 kW for 5 minutes;
[0117] (2.4) The alloy is turned over and the melting and refining process is repeated 5 times until the alloy is melted evenly. After the refining is completed, the furnace is naturally cooled, the gas is released and the furnace is taken out to obtain a titanium-based composite ingot.
[0118] (3) First, wire cutting is used to cut out the titanium-based composite ingot. The cylindrical casting is then evenly coated with Ti-1200 high temperature anti-oxidation coating on the surface of the casting, and after drying, the casting is wrapped with asbestos and tied with fine iron wire to prevent the asbestos from falling off; the casting is then placed in a muffle furnace and heated to 940°C for 30 minutes, while the upper and lower dies of the forging machine are heated to 940°C, and the casting is transferred from the muffle furnace to the forging machine at a speed of 0.01s -1 The forging is performed once at a speed of , the deformation during forging is not less than 60%, and air cooling is performed after forging to obtain a high-strength, toughness and wear-resistant titanium-based composite material, which is numbered TMC4.
[0119] Example 5 High-strength, toughness, and wear-resistant titanium-based composite material TMC5
[0120] The high-strength, toughness and wear-resistant titanium-based composite material of this embodiment comprises a matrix and a reinforcement phase, wherein the matrix comprises the following elemental components in mass percentage: Al 5.7%, Nb 2.9%, Fe 1.8%, Mo 1.6%, V 1.5%, Zr 0.92% and the balance Ti;
[0121] The reinforcing phases are TiB and La2O3. The mass percentage of the reinforcing phase TiB in the titanium-based composite material is 0.989%, and the mass percentage of La2O3 is 0.143%.
[0122] The method for preparing the high-strength, toughness and wear-resistant titanium-based composite material described in this embodiment comprises the following steps:
[0123] (1) According to the mass percentage of the elemental components of the matrix, raw materials including sponge titanium 791.11 g, high-purity aluminum 46.47 g, niobium-titanium alloy (Ti-53Nb) 54.10 g, iron particles 17.80 g, vanadium-aluminum alloy (Al-60V) 24.72 g, titanium-molybdenum alloy (Ti-32Mo) 49.43 g, and sponge zirconium 9.10 g were added, and then reinforcing phase titanium diboride 5.85 g and lanthanum oxide 1.43 g were added to obtain an alloy mixture; the titanium diboride was synthesized into TiB by an in-situ autogenous reaction, and the in-situ autogenous reaction was shown as follows: Ti+TiB2=2TiB.
[0124] (2) obtaining a titanium-based composite ingot by vacuum suspension melting the alloy mixture;
[0125] The specific process of vacuum suspension smelting includes the following steps:
[0126] (2.1) Placing the alloy mixture in a crucible;
[0127] (2.2) The vacuum degree in the vacuum water-cooled copper crucible suspension melting furnace was reduced to 3.8×10 -2 Pa, fill with argon 0.08MPa, turn on the power;
[0128] (2.3) melting at 80 kW for 5 minutes, melting at 100 kW for 5 minutes, melting at 120 kW for 5 minutes, melting at 150 kW for 5 minutes, and then refining at 150 kW for 5 minutes;
[0129] (2.4) The alloy is turned over and the melting and refining process is repeated 5 times until the alloy is melted evenly. After the refining is completed, the furnace is naturally cooled, the gas is released and the furnace is taken out to obtain a titanium-based composite ingot.
[0130] (3) First, wire cutting is used to cut out the titanium-based composite ingot. The cylindrical casting is then evenly coated with Ti-1200 high temperature anti-oxidation coating on the surface of the casting, and after drying, the casting is wrapped with asbestos and tied with fine iron wire to prevent the asbestos from falling off; the casting is then placed in a muffle furnace and heated to 940°C for 30 minutes, while the upper and lower dies of the forging machine are heated to 940°C, and the casting is transferred from the muffle furnace to the forging machine at a speed of 0.01s -1 The forging is performed once at a speed of , the deformation during forging is not less than 60%, and air cooling is performed after forging to obtain a high-strength, toughness and wear-resistant titanium-based composite material, which is numbered TMC5.
[0131] Example 6 High-strength, toughness, and wear-resistant titanium-based composite material TMC6
[0132] The high-strength, toughness and wear-resistant titanium-based composite material of this embodiment comprises a matrix and a reinforcement phase, wherein the matrix comprises the following elemental components in mass percentage: Al 5.6%, Nb 2.9%, Fe 1.8%, Mo 1.5%, V 1.4%, Zr 0.9% and the balance Ti;
[0133] The reinforcing phases are TiB and La2O3. The mass percentage of the reinforcing phase TiB in the titanium-based composite material is 1%, and the mass percentage of La2O3 is 0.2%.
[0134] The method for preparing the high-strength, toughness and wear-resistant titanium-based composite material described in this embodiment comprises the following steps:
[0135] (1) According to the mass percentage of the elemental components of the matrix, 795.55 g of raw materials including sponge titanium, 45.92 g of high-purity aluminum, 54.06 g of niobium-titanium alloy (Ti-53Nb), 17.78 g of iron particles, 23.53 g of vanadium-aluminum alloy (Al-60V), 46.32 g of titanium-molybdenum alloy (Ti-32Mo), and 8.9 g of sponge zirconium are added, and then 5.94 g of reinforcing phase titanium diboride and 2 g of lanthanum oxide are added to obtain an alloy mixture; the titanium diboride is synthesized into TiB by an in-situ autogenous reaction, and the in-situ autogenous reaction is shown as follows: Ti+TiB2=2TiB.
[0136] (2) obtaining a titanium-based composite ingot by vacuum suspension melting the alloy mixture;
[0137] The specific process of vacuum suspension smelting includes the following steps:
[0138] (2.1) Placing the alloy mixture in a crucible;
[0139] (2.2) The vacuum degree in the vacuum water-cooled copper crucible suspension melting furnace was reduced to 3×10 -2 Pa, fill with argon 0.05MPa, turn on the power;
[0140] (2.3) melting at 75 kW for 6 minutes, melting at 95 kW for 6 minutes, melting at 115 kW for 6 minutes, melting at 145 kW for 6 minutes, and then refining at 145 kW for 6 minutes;
[0141] (2.4) The alloy is turned over and the melting and refining process is repeated 6 times until the alloy is melted evenly. After the refining is completed, the furnace is naturally cooled, the gas is released and the furnace is taken out to obtain a titanium-based composite ingot.
[0142] (3) First, wire cutting is used to cut out the titanium-based composite ingot. The cylindrical casting is then evenly coated with Ti-1200 high temperature anti-oxidation coating on the surface of the casting, and after drying, the casting is wrapped with asbestos and tied with fine iron wire to prevent the asbestos from falling off; the casting is then placed in a muffle furnace and heated to 1000°C for 40 minutes, while the upper and lower dies of the forging machine are heated to 1000°C, and the casting is transferred from the muffle furnace to the forging machine at a speed of 0.02s -1 The forging is performed once at a speed of , the deformation amount of forging is not less than 60%, and air cooling is performed after forging to obtain a high-strength, toughness and wear-resistant titanium-based composite material, which is numbered TMC6.
[0143] Example 7 High-strength, toughness, and wear-resistant titanium-based composite material TMC7
[0144] The high-strength, toughness and wear-resistant titanium-based composite material of this embodiment comprises a matrix and a reinforcement phase, wherein the matrix comprises the following elemental components in mass percentage: Al 7%, Nb 4%, Fe 3%, Mo 2%, V 2%, Zr 1.5% and the balance is Ti;
[0145] The reinforcing phases are TiB and La2O3. The mass percentage of the reinforcing phase TiB in the titanium-based composite material is 2%, and the mass percentage of La2O3 is 1%.
[0146] The method for preparing the high-strength, toughness and wear-resistant titanium-based composite material described in this embodiment comprises the following steps:
[0147] (1) According to the mass percentage of the elemental components of the matrix, 713.32 g of raw materials of sponge titanium, 54.97 g of high-purity aluminum, 73.21 g of niobium-titanium alloy (Ti-53Nb), 29.1 g of iron particles, 32.33 g of vanadium-aluminum alloy (Al-60V), 60.63 g of titanium-molybdenum alloy (Ti-32Mo), and 14.55 g of sponge zirconium are added, and then 11.89 g of reinforcing phase titanium diboride and 10 g of lanthanum oxide are added to obtain an alloy mixture; the titanium diboride is synthesized into TiB by an in-situ autogenous reaction, and the in-situ autogenous reaction is shown as follows: Ti+TiB2=2TiB.
[0148] (2) obtaining a titanium-based composite ingot by vacuum suspension melting the alloy mixture;
[0149] The specific process of vacuum suspension smelting includes the following steps:
[0150] (2.1) Placing the alloy mixture in a crucible;
[0151] (2.2) The vacuum degree in the vacuum water-cooled copper crucible suspension melting furnace was reduced to 5×10 -2 Pa, fill with argon 0.1MPa, turn on the power;
[0152] (2.3) melting at 85 kW for 4 minutes, melting at 105 kW for 4 minutes, melting at 125 kW for 4 minutes, melting at 155 kW for 4 minutes, and then refining at 155 kW for 4 minutes;
[0153] (2.4) The alloy is turned over and the melting and refining process is repeated 7 times until the alloy is melted evenly. After the refining is completed, the furnace is naturally cooled, the gas is released and the furnace is taken out to obtain a titanium-based composite ingot.
[0154] (3) First, wire cutting is used to cut out the titanium-based composite ingot. The cylindrical casting is then evenly coated with Ti-1200 high temperature anti-oxidation coating on the surface of the casting, and after drying, the casting is wrapped with asbestos and tied with fine iron wire to prevent the asbestos from falling off; the casting is then placed in a muffle furnace and heated to 900°C for 30 minutes, while the upper and lower dies of the forging machine are heated to 900°C, and the casting is transferred from the muffle furnace to the forging machine at a speed of 0.02s -1 The forging is performed once at a speed of , the deformation amount of forging is not less than 60%, and air cooling is performed after forging to obtain a high-strength, toughness and wear-resistant titanium-based composite material, which is numbered TMC7.
[0155] Example 8 High-strength, toughness, and wear-resistant titanium-based composite material TMC8
[0156] The high-strength, toughness and wear-resistant titanium-based composite material of this embodiment comprises a matrix and a reinforcement phase, wherein the matrix comprises the following elemental components in mass percentage: Al 7%, Nb 3.3%, Fe 2%, Mo 2%, V 1.4%, Zr 1% and the balance is Ti;
[0157] The reinforcing phases are TiB and La2O3. The mass percentage of the reinforcing phase TiB in the titanium-based composite material is 0.2%, and the mass percentage of La2O3 is 0.1%.
[0158] The method for preparing the high-strength, toughness and wear-resistant titanium-based composite material described in this embodiment comprises the following steps:
[0159] (1) According to the mass percentage of the elemental components of the matrix, 759.76 g of raw materials of sponge titanium, 60.49 g of high-purity aluminum, 62.08 g of niobium-titanium alloy (Ti-53Nb), 19.94 g of iron particles, 23.26 g of vanadium-aluminum alloy (Al-60V), 62.31 g of titanium-molybdenum alloy (Ti-32Mo), and 9.97 g of sponge zirconium are added, and then 1.19 g of reinforcing phase titanium diboride and 1 g of lanthanum oxide are added to obtain an alloy mixture; the titanium diboride is synthesized into TiB by an in-situ autogenous reaction, and the in-situ autogenous reaction is shown as follows: Ti+TiB2=2TiB.
[0160] (2) obtaining a titanium-based composite ingot by vacuum suspension melting the alloy mixture;
[0161] The specific process of vacuum suspension smelting includes the following steps:
[0162] (2.1) Placing the alloy mixture in a crucible;
[0163] (2.2) The vacuum degree in the vacuum water-cooled copper crucible suspension melting furnace was reduced to 3×10 -2 Pa, fill with argon 0.05MPa, turn on the power;
[0164] (2.3) melting at 80 kW for 5 minutes, melting at 100 kW for 5 minutes, melting at 120 kW for 5 minutes, melting at 150 kW for 5 minutes, and then refining at 150 kW for 5 minutes;
[0165] (2.4) The alloy is turned over and the melting and refining process is repeated 5 times until the alloy is melted evenly. After the refining is completed, the furnace is naturally cooled, the gas is released and the furnace is taken out to obtain a titanium-based composite ingot.
[0166] (3) First, wire cutting is used to cut out the titanium-based composite ingot. The cylindrical casting is then evenly coated with Ti-1200 high temperature anti-oxidation coating on the surface of the casting, and after drying, the casting is wrapped with asbestos and tied with fine iron wire to prevent the asbestos from falling off; the casting is then placed in a muffle furnace and heated to 980°C for 40 minutes, and the upper and lower dies of the forging machine are heated to 980°C at the same time, and the casting is transferred from the muffle furnace to the forging machine at a speed of 0.01s -1 The forging is performed once at a speed of , the deformation amount of forging is not less than 60%, and air cooling is performed after forging to obtain a high-strength, toughness and wear-resistant titanium-based composite material, which is numbered TMC8.
[0167] Performance Testing
[0168] (1) Mechanical properties
[0169] from Figure 2 As can be seen from the data in Tables 2 and 3, the comprehensive mechanical properties of the forged state are greatly improved compared with those of the cast state, that is, forging is conducive to greatly improving the comprehensive performance of titanium-based composite materials, among which TMC4 has the best comprehensive mechanical properties, combining high strength and toughness with high hardness.
[0170] Table 2 Comparison of mechanical properties of TMC0-TMC5 as-cast
[0171]
[0172] Table 3 Comparison of mechanical properties of TMC0-TMC5 in forging state
[0173]
[0174] (2) Organizational characteristics
[0175] Figure 3 It is an optical microscope image of TMC0-TMC5 in the casting state. It can be seen from the image that the tissues of TMC0, TMC3, TMC4 and TMC5 are Widmanstätten structures, and the tissues of TMC1 and TMC2 are basketweave structures.
[0176] Figure 4 This is the SEM image of the cast TMC0-TMC5. It can be seen from the figure that the distribution of the reinforcement phase in the alloy matrix is not uniform, and there are long rod-shaped, granular and block-shaped reinforcement phases.
[0177] Figure 5 The optical microscope images of TMC0-TMC5 forging states show that after forging, TMC1 and TMC2 are equiaxed structures, while TMC0, TMC3, TMC4, and TMC5 are dual-state structures. Compared with TMC1 and TMC2, although TMC3, TMC4, and TMC5 correspond to fewer reinforcing phases, the denser structure and dual-state structure contribute positively to the strength, so their strengths are relatively close.
[0178] Figure 6 This is the SEM image of the forged state of TMC0-TMC5. It can be seen from the figure that compared with the cast state, the size of the forged reinforcement phase is reduced, and the reinforcement phase can greatly improve the hardness.
[0179] Figure 7 This is the element surface distribution diagram of TMC3. It can be seen from the figure that the B element and the O element in the matrix are segregated, and the distribution of TiB and La2O3 in the matrix is determined.
[0180] Those skilled in the art will readily appreciate other embodiments of the present application after considering the specification and practicing the contents disclosed herein. The present application is intended to cover any variations, uses or adaptations of the present application, which follow the general principles of the present application and include common knowledge or customary technical means in the art that are not disclosed in the present application. The specification and embodiments are to be regarded as exemplary only, and the present application is not limited to the precise structures described above and shown in the drawings, and various modifications and changes may be made without departing from the scope thereof.
Claims
1. A high-strength, toughness and wear-resistant titanium-based composite material, characterized in that: The invention comprises a matrix and a reinforcement phase, wherein the matrix comprises the following element components in mass percentage: Al 5.6-7%, Nb 2.9-4%, Fe 1.8-3%, Mo 1.5-2%, V 1.4-2%, Zr 0.9-1.5% and the balance Ti; The reinforcement phase is selected from at least two of TiB, TiC or La2O3, and the mass percentage of the reinforcement phase in the titanium-based composite material is 0.3-3%.
2. The high-strength, toughness and wear-resistant titanium-based composite material according to claim 1, characterized in that: The invention comprises a matrix and a reinforcement phase, wherein the matrix comprises the following elemental components in mass percentage: Al 5.7%, Nb 2.9%, Fe 1.8%, Mo 1.6%, V 1.5%, Zr 0.92% and the balance Ti; The reinforcement phase is TiB and La2O3, and the mass percentage of the reinforcement phase in the titanium-based composite material is 0.3-1.2%.
3. The method for preparing the high-strength, toughness and wear-resistant titanium-based composite material according to claim 1, characterized in that: The steps include: (1) preparing raw materials according to the mass percentage of the elemental components of the matrix, and then adding a reinforcing phase to obtain an alloy mixture; (2) obtaining a titanium-based composite ingot by vacuum suspension melting the alloy mixture; (3) After the ingot is kept warm in the α+β phase region, it is transferred to a forging machine for isothermal forging to obtain a high-strength, toughness, and wear-resistant titanium-based composite material.
4. The preparation method according to claim 3, characterized in that: In step (1), the element composition of the matrix is Al 5.6-7%, Nb 2.9-4%, Fe 1.8-3%, Mo 1.5-2%, V 1.4-2%, Zr 0.9-1.5% and the balance is Ti; The reinforcement phase is selected from at least two of TiB, TiC or La2O3, and the mass percentage of the reinforcement phase in the titanium-based composite material is 0.3-3%.
5. The preparation method according to claim 3, characterized in that: In step (2), the specific process of the vacuum suspension smelting comprises the following steps: (2.1) Placing the alloy mixture in a crucible; (2.2) Evacuate the vacuum water-cooled copper crucible suspension smelting furnace, fill it with argon, and turn on the power supply; (2.3) Melting at 75-155 kW, followed by refining at 145-155 kW; (2.4) The alloy is turned over and the melting and refining process is repeated for at least 5 times until the alloy is melted evenly. After the refining is completed, the furnace is naturally cooled, the gas is released and the furnace is taken out to obtain a titanium-based composite ingot.
6. The preparation method according to claim 3, characterized in that: In step (3), the process of transferring the casting to the forging machine for isothermal forging after heat preservation is to place the titanium-based composite material ingot in a muffle furnace and heat it to the α+β phase region for heat preservation, while heating the upper and lower molds of the forging machine to the α+β phase region temperature, and transferring the casting from the muffle furnace to the forging machine for a forging, and air cooling after forging to obtain a high-strength, toughness and wear-resistant titanium-based composite material.
7. The preparation method according to claim 4, characterized in that: In step (1), the elements Ti, Al, Nb, Fe, Mo, V, and Zr in the matrix are added in the form of sponge titanium, high-purity aluminum, niobium-titanium alloy, iron particles, titanium-molybdenum alloy, vanadium-aluminum alloy, and sponge zirconium, respectively; TiB, TiC, and La2O3 in the reinforcement phase are added in the form of titanium diboride, graphite powder, and lanthanum oxide, respectively.
8. The preparation method according to claim 7, characterized in that: The titanium diboride and the graphite powder are synthesized into TiB and TiC respectively through in-situ autogenous reaction, and the in-situ autogenous reaction is shown in the following formula: Ti+TiB2=2TiB, Ti+C=TiC.
9. The preparation method according to claim 5, characterized in that: The vacuum degree in step (2.2) is 3×10 -2 ~5×10 -2 Pa, filled with argon 0.05~0.1MPa.
10. The preparation method according to claim 5, characterized in that: In the step (2.3), the smelting process is carried out in sequence at powers of 75-85kw, 95-105kw, 115-125kw, and 145-155kw, and then refined at a power of 145-155kw.
11. The preparation method according to claim 10, characterized in that: In the step (2.3), the specific process of the smelting is smelting at a power of 75 to 85 kw for 4 to 6 minutes, smelting at a power of 95 to 105 kw for 4 to 6 minutes, smelting at a power of 115 to 125 kw for 4 to 6 minutes, smelting at a power of 145 to 155 kw for 4 to 6 minutes, and then refining at a power of 145 to 155 kw for 4 to 6 minutes.
12. The preparation method according to claim 6, characterized in that: The deformation amount of the forging is not less than 60%.
13. The preparation method according to claim 6, characterized in that: The pretreatment process of the titanium-based composite material ingot is to first cut a cylindrical casting on the titanium-based composite material ingot by wire cutting; then evenly apply high-temperature anti-oxidation coating on the surface of the casting, wrap the casting with asbestos after drying, and bundle it.
14. The preparation method according to claim 13, characterized in that: The high temperature anti-oxidation coating is Ti-1200 high temperature anti-oxidation coating.